Differences in lightness, chroma, and hue in the anterior teeth of quinquagenarians and septuagenarians - Eiffler, Constantin; Cevirgen, Engin Bernhard Haydar; Helling, Stephan; Zornek, Juanita; Pritsch, Maria; Hassel, Alexander J. (Clinical oral investigations, 2010)
The purpose of this study was to evaluate, for both genders and two elderly age groups, differences in lightness, chroma, and hue of pairs of natural anterior teeth, so that more accurate information on color would be available for the production of dentures with a natural appearance. The subjects in the younger group (YG) were 54 to 56 years of age, those in the older group 73 to 75 (N = 195, 48% women). Tooth color was measured using a spectrophotometer. Mixed models were calculated for each pair of teeth, with gender as a fixed factor. Gender did not have a significant effect in either age group. In both groups, differences in chroma between upper canines and lateral incisors and in lightness and hue between upper and lower canines were observed. In the YG, additional differences were found, with the only exception of the comparison between upper central and lateral incisors. The nongender-specific color differences observed should be considered when producing denture teeth for these groups of patients, in order to come as close as possible to the natural color ideal.
Published online: 18 August 2009
Gesehen am 06.03.2023